THE ROLE OF ACCOUNTING IN MANAGEMENT. - Coleman, R. W. (The Accounting Review, 1949)
The significance of facts is mere important than the facts themselves, and if accountants know the significance, people may even forget the facts. This thought, expressed by Oliver Wendell Holmes, seems pertinent when appraising the relation of accounting to management. It is the managerial significance of business data that is really important. Ideally, the greatest aid that accounting could offer management would be to assist in the accomplishment of its objectives through the preparation and interpretation of appropriate statements. The techniques whereby business transactions are recorded and their values eventually placed in the statements are of secondary importance. The relation between accounting and management has been commonly expressed by the phrase that accounting is a tool of management. This means that it is possible for management, through the use of proper accounting reports, to make decisions and to formulate policies based on recorded business data. The function of interpreting accounting records has been accepted by accountants.